Food marketing: the influence of organic greenwash towards Malaysian consumers' trust: a conceptual paper / Muhammad Azman Ibrahim, Rafiatul Adlin Mohd Ruslan and Thong Foong Yen - Ibrahim, Muhammad Azman; Mohd Ruslan, Rafiatul Adlin; Thong, Foong Yen (Universiti Teknologi MARA, 2021)
This research is focusing on the influence of greenwash on Malaysian consumers' trust towards organic food products. Malaysian consumers are becoming more aware and understand the importance of organic food products. Although Malaysia's organic market is still niche, many organic food products and organic retail/shops are available to purchase it. However, Malaysian consumers are concerned with the validity and credibility of organic food products, as many organic food products are from the local and importing country. Organic food products can relate to the greenwash that will impact consumers' trust towards organic food products. Therefore, the conceptual framework is developed by proposing four constructs - organic greenwashing, organic perceived risk, organic confusion and organic trust. The research will also focus on Malaysian consumers who have organic purchasing experience or intend to purchase organic food products. This conceptual paper will give insightful ideas for future research and give benefits to organic food retailing.